Tombs of Anak - Peretti, Frank E. (Wheaton, Ill. : Crossway, 1990)
When Jay and Lila Cooper enter the cave-tombs of Anak with their archaeologist father, they hope to find a co-worker who has unaccountably disappeared. Instead, they stumble onto a frightening religion and new mysteries that soon put them all in incredible danger. The third book of the Cooper Kids Adventures.
Keywords: Detective and mystery stories